Análisis sectorial del consumo de la electricidad durante la pandemia – COVID-19: evidencia para los mercados no regulado y regulado en Colombia (2022)
In this investigation, through a model of seemingly unrelated equations, we conduct a sectoral analysis of electricity consumption during the pandemic - COVID-19 for the main sectors that make up the Unregulated and Regulated markets in Colombia. Using daily data for the unregulated market and monthly data for the regulated market between February 2015 and May 2021, we find statistically significant evidence of a recomposition in electricity consumption with the pandemic from the mandatory preventive confinement, established by Decree 457 of 2020, the average consumption in the residential sector increased by 16.9%, since they were carrying out their work from their residences. On the contrary, those sectors of the unregulated market subject to quarantines presented a fall. However, in sectors that were not subjected to mandatory preventive isolation, since they were necessary to satisfy the supply of basic services such as health, food (agriculture) and water supply, their coefficients for strict confinement were not statistically significant and presented an increase in electricity consumption.